Using a typed mind map as a data model in a TDD DICE system - Chien, Li-Ren (Array, 2008)
Summary: This paper introduces a new Typed Mind Map extension for a data model in a parse-tree-based online referee system with a TDD (Test-Driven Development) model and DALM (DICE adaptive learning model) model named DICE. TypedMindMaps and a semantic node are defined by OWL-DL. Typed Mind Maps are now widely used in the DICE system as a uniform data model for the system, instructors, learners and materials. The Mind Maps are used for system configuration, system deployment, learner's information, organization of training materials, answer parsing and some widgets. An implementation based on this data model has been working for years in a real teaching and learning environment